UPAYA PENINGKATAN MUTU DAN EFISIENSI PROSES PENGERINGAN JAGUNG DENGAN MIXED-ADSORPTION DRYER - Luqman Buchori; Mohamad Djaeni; Laeli Kurniasari (Reaktor, 2013)
THE EFFORT OF EFFICIENCY AND QUALITY IMPROVEMENT ON CORN DRYING PROCESS USING MIXED-ADSORPTION DRYER. The main problem in corn drying process is the low of energy efficiency (50%) and quality products. Consequently, operating costs in large for fuel consumption and the short shelf life of corn. Zeolite adsorption dryers have the potential to overcome this problem. This research aims to study composition of corn-zeolite and the effect of temperature on drying speed and protein and fat content in corn. Research variables are the ratio of corn and zeolite (1:0, 1:3, 1:1, 3:1) and intake air temperature (room temperature, 30oC, 40oC, 50oC). Sampling for moisture testing performed every 15 minutes. For energy purposes also calculated the energy efficiency (h) based on the amount of heat used to evaporate water from the corn (Qevap) divided by the total heat requirement to regenerate the zeolite and raising the air temperature (Qintr). Profiles of temperature and water in the mixed adsorption dryer are also studied. The results showed that the greater number of zeolite used, the water content of the final outcome a little more drying, protein and fat content of the final result of drying is relatively constant. The larger intake air temperature, the water content of the less drying results, protein content decreases, and the fat content does not change/relatively constant. The best variable was a ratio of corn: zeolite is 1:3 and air temperature was 50oC. While the variables that are suitable and in accordance with ISO standards for dry foods (14%) are air temperature of between 40oC and 50oC with a ratio of corn:zeolite is 1:3. The energy efficiency of 81.23% is obtained. Modeling done with FEMLAB (COMSOL) can describe the moisture content and temperature profiles in the corn and zeolite. Keywords: corn; drying; energy efficiency; mixed adsorption dryer; zeolite Abstrak Masalah utama proses pengeringan jagung adalah rendahnya efisiensi energi (50%) dan mutu produk sehingga beban biaya operasi besar untuk konsumsi bahan bakar. Pengering adsorpsi dengan zeolite berpotensi untuk mengatasi permasalahan ini. Penelitian ini bertujuan untuk mempelajari pengaruh komposisi jagung-zeolite dan suhu terhadap kecepatan pengeringan dan kandungan protein dan lemak di dalam jagung. Penelitian dilakukan dengan variabel berubah yaitu rasio antara jagung dan zeolit (1:0, 1:3, 1:1, 3:1) dan suhu udara masuk (suhu kamar, 30oC, 40oC, 50oC). Pengambilan sampel untuk pengujian kadar air dilakukan setiap 15 menit. Untuk keperluan energi dihitung pula efisiensi energi (h) berdasarkan jumlah panas yang digunakan untuk menguapkan air dari jagung (Qevap) dibagi dengan kebutuhan panas total untuk meregenerasi zeolit dan menaikkan suhu udara (Qintr). Profil temperatur dan air di dalam mixed adsorption dryer juga dipelajari. Hasil penelitian menunjukkan bahwa semakin banyak jumlah zeolit yang digunakan, kadar air hasil akhir pengeringan makin sedikit, kadar protein dan lemak hasil akhir pengeringan relatif konstan. Semakin besar suhu udara masuk pengering, kadar air hasil pengeringan makin sedikit, kadar protein semakin menurun, dan kadar lemak tidak berubah/relatif konstan. Variabel yang terbaik adalah variabel dengan rasio jagung:zeolit yaitu 1:3 dan menggunakan suhu udara pengering 50oC. Sedangkan variabel yang cocok dan sesuai dengan standar SNI untuk makanan kering (14%) adalah variabel dengan menggunakan suhu udara pengering antara 40oC dan 50oC dengan rasio berat jagung : zeolit adalah 1:3. Efisiensi energi diperoleh sebesar 81,23%. Pemodelan yang dilakukan dengan Femlab (COMSOL) dapat menggambarkan profil kandungan air dan suhu di dalam jagung dan zeolit. Kata kunci : jagung; pengeringan; efisiensi energi; mixed adsorption dryer; zeolit